Microelectronic converter of gas consumption based on two bipolar transistors with active inductive element - Osadchuk, Volodymyr; Osadchuk, Olexandre; Yaremishena, Nataliia (Scientific Works of Vinnytsia National Technical University, 2015)
The scheme of microelectronic converter of gas consumption, based on two bipolar transistors with active element is suggested. The given scheme realizes self-excited oscillator where gas consumption conversion is realized into output frequency signal. Analytical expressions of conversion function and sensitivity equation are obtained. REFERENCES 1. Кремлевский П. П. Расходомеры и счетчики количества / П. П. Кремлевский. – Л. : Машиностроение, 1975. – 776 с. 2. Осадчук О. В. Мікроелектронні частотні перетворювачі на основі структур з від’ємним опором / О. В. Осадчук. – Вінниця: УНІВЕРСУМ, 2001. – 303 с. 3. Разевич В. Д. Применение программ Р-САД и Pspise для схемотехнического моделирования на ПЭВМ. Выпуск 2: Модели компонентов аналоговых устройств / В. Д. Разевич. М.: Радио и связь. 1992. – 64 с.